(untitled) - Weinstein, Carol Simon (New York, 2011)
Stressing the need to build caring, supportive relationships with and among students, Elementary Classroom Management: Lessons from Research and Practice offers research-based guidance on effective classroom management. It addresses current concerns about student motivation and helps prospective and beginning teachers develop a philosophy of classroom management that focuses on building connections with students and creating safe, caring classrooms.
Keywords: Classroom management,Education, Elementary,Giáo dục tiểu học,Quản lý lớp học; United States,Hoa Kỳ